Evaluation of the impact of fluoride in drinking water and tea on the enamel of deciduous and permanent teeth - Asu Çakır; Tuğçe Nur Şahin (BMC, 2023)
Abstract Background Systemic fluoride intake is predominantly derived from drinking water and tea. It's been noted that water and tea containing fluoride, within the boundaries set by the World Health Organization, can lessen the prevalence of dental caries. A review of the literature did not uncover any study that has examined the impact of fluoride in bottled drinking water and tea on enamel of deciduous and permanent teeth. Thus, we assessed the effects of fluoride present in seven different brands of bottled water from distinct geographical regions of Turkey, and a type of tea produced and packaged in Turkey, on the enamel of deciduous and permanent teeth. Materials and methods Fluoride analysis was performed on drinking water sourced from seven different regions of Turkey and a brand of tea brewed with these waters. The tea was harvested and packaged in Turkey. The analysis was conducted using an ion-selective electrode. In total, 112 tooth enamel samples (56 deciduous molars and 56 permanent molars) were randomly divided into eight distinct groups. These were kept in water for 15 min and tea for 15 min every day for a month. The eighth group was treated with fluoride gel prior to tea and water applications. The amount of fluoride in the tooth enamel structure was evaluated using an SEM EDX device before and after the experiment. Results Statistically significant differences were found in fluoride content of enamel between water brands and tooth type (deciduous and permanent teeth). Fluoride levels were higher in the enamel of deciduous teeth than in permanent teeth. Conclusion Regular exposure of enamel samples to black tea and water led to an increase in fluoride levels in the enamel; thus, regular consumption of black tea and fluoride water could help reduce the prevalence of dental caries.